The value of enzyme preparations added to beef cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This was our second test to determine the value of various enzyme preparations added to beef cattle rations. The first involved amylase and a combination of amylase and protease. Amylase apparently depressed the appetite or feed consumption, which resulted in decreased rate of gain. The combination of amylase and protease appeared to increase rate of gain at the beginning of the test; however, gains decreased as the test progressed and ended with the average daily gain being less than for control animals. This test involved a combination of amylase and protease and also this combination plus cellulose in the wintering phase. One lot received protease only in the fattening phase.
Keywords: Beef; Enzyme; Average daily gain; Amylase; Protease